Study on the acoustic emission and thermal infrared signal characteristics of granite with freeze-thaw damage in cycle loading process - Liang, Yufei; Yang, Qingwen; Zhu, Ling; Jiang, Tao; Gao, Meibeng (Frontiers in Earth Science, 2022)
Acoustic emission and thermal infrared signals are related to the process of rock breaking. In this paper, the acoustic emission and thermal infrared signals of rock are obtained during the loading process of indoor granite freeze-thaw cycle test and uni-axial compression test. Then the acoustic emission signals sent out during rock breaking are analyzed by short-time Fourier transform to get the peak frequency. IR thermographic sensor is applied to monitor and record the temperature change on the surface of rock so as to get the influence of thermal infrared radiation characteristics during rock materials deformation and breaking. Under the same axial stress, the samples passing through more freeze-thaw cycles have higher surface temperature. Both acoustic emission and thermal infrared temperature show that tensile failure is the main failure factor to granite samples. As freeze-thaw effect results in more micro fissures inside rock, the granite samples develop in the tendency of large breakage increases and small breakage decreases. This phenomenon shows that freeze-thaw cycle could restrict the heat release of granite sample.